CONTRACTOR DECISION MAKING ON CONTINUING A SUSPENDED PROJECT USING AHP-TOPSIS (A CASE STUDI OF THE NINES PLAZA & RESIDENCE BSD PROJECT) - Jiwo Waskito; Endah Kurniyaningrum (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Suspended construction projects pose multidimensional challenges and necessitate accountable follow-up decision-making from the contractor’s perspective. This study develops a multi-criteria decision making (MCDM) framework to determine the most appropriate alternative for continuing a suspended high-rise building project, using the Nines Plaza and Residence BSD as a case study. The Analytic Hierarchy Process (AHP) is applied to derive priority weights for nine decision criteria, while the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is used to rank four decision alternatives for project continuation. Decision robustness is examined through contextual scenario variations, respondent clustering based on expertise, and sensitivity analysis of criterion dominance. The results indicate that cost and financing are the most influential criteria, and continuing the project through a strategic partnership (joint venture) emerges as the best alternative. Robustness testing confirms that the decision outcome is stable and not driven by a single dominant criterion, demonstrating that the integrated AHP–TOPSIS approach is a suitable decision-support tool for contractors dealing with suspended construction projects.